Neutrophil-specific STAT4 deficiency attenuates atherosclerotic burden and improves plaque stability via reduction in neutrophil activation and recruitment into aortas of Ldlr−/− mice - Keeter, W. Coles; Moriarty, Alina K.; Akers, Rachel; Ma, Shelby; Mussbacher, Marion; Nadler, Jerry L.; Galkina, Elena V. (Frontiers in Cardiovascular Medicine, 2023)
Background and aims Neutrophils drive atheroprogression and directly contribute to plaque instability. We recently identified signal transducer and activator of transcription 4 (STAT4) as a critical component for bacterial host defense in neutrophils. The STAT4-dependent functions of neutrophils in atherogenesis are unknown. Therefore, we investigated a contributory role of STAT4 in neutrophils during advanced atherosclerosis. Methods We generated myeloid-specific Stat4ΔLysMLdlr−/−, neutrophil-specific Stat4ΔS100A8Ldlr−/−, and control Stat4fl/flLdlr−/− mice. All groups were fed a high-fat/cholesterol diet (HFD-C) for 28 weeks to establish advanced atherosclerosis. Aortic root plaque burden and stability were assessed histologically by Movat pentachrome staining. Nanostring gene expression analysis was performed on isolated blood neutrophils. Flow cytometry was utilized to analyze hematopoiesis and blood neutrophil activation. In vivo homing of neutrophils to atherosclerotic plaques was performed by adoptively transferring prelabeled Stat4ΔLysMLdlr−/− and Stat4fl/flLdlr−/− bone marrow cells into aged atherosclerotic Apoe−/− mice and detected by flow cytometry. Results STAT4 deficiency in both myeloid-specific and neutrophil-specific mice provided similar reductions in aortic root plaque burden and improvements in plaque stability via reduction in necrotic core size, improved fibrous cap area, and increased vascular smooth muscle cell content within the fibrous cap. Myeloid-specific STAT4 deficiency resulted in decreased circulating neutrophils via reduced production of granulocyte-monocyte progenitors in the bone marrow. Neutrophil activation was dampened in HFD-C fed Stat4ΔLysMLdlr−/− mice via reduced mitochondrial superoxide production, attenuated surface expression of degranulation marker CD63, and reduced frequency of neutrophil-platelet aggregates. Myeloid-specific STAT4 deficiency diminished expression of chemokine receptors CCR1 and CCR2 and impaired in vivo neutrophil trafficking to atherosclerotic aorta. Conclusions Our work indicates a pro-atherogenic role for STAT4-dependent neutrophil activation and how it contributes to multiple factors of plaque instability during advanced atherosclerosis in mice.